Characterization of the Manganese Oxide Scales Formed on Rolled Lead Anodes From a Commercial Zinc Electrowinning Operation - T. T. Chen (The Minerals, Metals and Materials Society, 2009)
The manganese oxide scales, consisting mainly of MnO2, characteristically occur in banded colloform structures which adhere to porous layers of PbSO4 and PbO2 that oxidized from the rolled Pb-0.7% Ag anodes. Hydrous Mn oxides, Mn3O4 and amorphous Mn oxides are believed to be also present. Tiny particles of gypsum, PbSO4, SrSO4 and AgCl are entrapped in the colloform masses. The gypsum originated from the Zn electrolyte; strontium carbonate was added to the ZnSO4 solution to control Pb, and silver originated from the anodes. Some of the colloform bands contain minor amounts of Pb, implying a limited degree of dissolution of the Pb during electrolysis. Other colloform bands incorporate trace amounts of Zn. Colloform structures permeated with silica gel are presumably caused by the high silica content of the electrolyte.